Pengaruh program latihan plyometric terhadap peningkatan kemampuan jumping smash pada club bola voli power steller samarinda tahun 2025/2026 - Mu'ammar mu'ammar (IKIP PGRI KALIMANTAN TIMUR, 2026)
Abstract. This research was motivated by the low jumping smash ability of athletes at Power Steller Volleyball Club Samarinda, as observed on December 18, 2025. The identified problems included low jump height, insufficient striking power, and frequent technical errors during jumping smash execution. Meanwhile, plyometric training, which has theoretically been proven to enhance leg muscle explosive power, had not been systematically implemented at the club. Therefore, this study aimed to determine the effect of a plyometric training program on improving jumping smash ability among athletes at Power Steller Volleyball Club Samarinda in 2025/2026. This study employed a pre-experimental research design with a one group pretest-posttest pattern. The research subjects consisted of 15 female volleyball players from Power Steller Club selected through saturated sampling technique. The instrument used was a vertical jump test to measure jumping smash ability. The intervention consisted of a plyometric skipping training program conducted over 6 weeks with a frequency of 2 sessions per week for a total of 12 sessions. Data analysis techniques included the Kolmogorov-Smirnov normality test, Levene's homogeneity test, and hypothesis testing through simple linear regression analysis using SPSS.